2006
DOI: 10.1074/jbc.m513009200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Association, Mechanism of Action, and Structure of Arabidopsis Embryonic Factor 1 (FAC1)

Abstract: Embryonic factor 1 (FAC1) is one of the earliest expressed plant genes and encodes an AMP deaminase (AMPD), which is also an identified herbicide target. This report identifies an N-terminal transmembrane domain in Arabidopsis FAC1, explores subcellular fractionation, and presents a 3.3-Å globular catalytic domain x-ray crystal structure with a bound herbicide-based transition state inhibitor that provides the first glimpse of a complete AMPD active site. FAC1 contains an (␣/␤) 8 -barrel characterized by loops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 53 publications
1
47
0
Order By: Relevance
“…Nevertheless, the identification of this protein implies a conserved role for it, both on bacterial membranes and evidently on the mitochondrial outer membrane in plants. Another well-conserved protein is Embryonic Factor1 (FAC1; At2g38280.1), for which the subcellular location has long been discussed (Han et al, 2006), but in this study we report an outer mitochondrial membrane localization for this protein, on the basis of both proteomic and GFP evidence. Interestingly, like PECT1 and MIRO1, it has been observed that plants have a seed-lethal phenotype when FAC1 is knocked out (Xu et al, 2005;Meinke et al, 2008), indicating a vital role for these outer mitochondrial membrane proteins in Arabidopsis development.…”
Section: Proteins Involved In Signaling and Catabolic Processesmentioning
confidence: 82%
“…Nevertheless, the identification of this protein implies a conserved role for it, both on bacterial membranes and evidently on the mitochondrial outer membrane in plants. Another well-conserved protein is Embryonic Factor1 (FAC1; At2g38280.1), for which the subcellular location has long been discussed (Han et al, 2006), but in this study we report an outer mitochondrial membrane localization for this protein, on the basis of both proteomic and GFP evidence. Interestingly, like PECT1 and MIRO1, it has been observed that plants have a seed-lethal phenotype when FAC1 is knocked out (Xu et al, 2005;Meinke et al, 2008), indicating a vital role for these outer mitochondrial membrane proteins in Arabidopsis development.…”
Section: Proteins Involved In Signaling and Catabolic Processesmentioning
confidence: 82%
“…Although the intracellular metabolism of this compound in plants has not been examined, its mode of action is presumably similar because coformycin 5#-phosphate is a potent inhibitor of rabbit muscle AMPD (Frieden et al, 1980). The recently solved x-ray crystal structure of FAC1 complexed with coformycin 5#-phosphate confirmed this mode of inhibition and also provided the first glimpse of a complete AMPD active site in plants (Han et al, 2006). Coformycin and carbocyclic coformycin are also inhibitors of mammalian adenosine deaminase (Frieden et al, 1980;Dancer et al, 1997), but the lack of this enzyme in plants ( Le Floc'h et al, 1982;Yabuki and Ashihara, 1991;Dancer et al, 1997) supports the argument that AMPD is the primary intracellular target once these compounds are converted to their respective nucleotide derivatives.…”
mentioning
confidence: 72%
“…These combined observations demonstrate that a functional AMPD enzyme effectively prevents the detrimental expansion of the adenine nucleotide pool in response to increased salvage synthesis of adenine. This functional significance can be attributed to a dramatic K m and V max ATP activation, as reported for the endogenous Catharanthus roseus (Yabuki and Ashihara, 1992) and recombinant Arabidopsis (Han et al, 2006) enzymes. This combined regulatory effect is not seen with orthologs in the animal kingdom, which suggests that plant AMPD may have evolved this property to compensate for the lack of an alternate AMP catabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations